Optimal Roving Winding on Toroidal Parts of Composite Frames - Mlýnek, Jaroslav; Rahimian Koloor, Seyed Saeid; Knobloch, Roman (Polymers, 2023)
Frames made of polymer composites are increasingly used in the aerospace, automotive, and agricultural industries. A frequently used technology in the production line of composite frames is winding rovings onto a non-load-bearing frame to form the structure using an industrial robot and a winding head, which is solidified through a subsequent heat-treatment pressure process. In this technology, the most difficult procedure is the winding of the curved parts of a composite frame. The primary concern is to ensure the proper winding angles, minimize the gaps and overlaps, and ensure the homogeneity of the wound layers. In practice, the curved frame parts very often geometrically form sections of a torus. In this work, the difficulty of achieving a uniform winding of toroidal parts is described and quantified. It is shown that attaining the required winding quality depends significantly on the geometrical parameters of the torus in question. A mathematical model with a detailed procedure describing how to determine the number of rovings of a given width on toroidal parts is presented. The results of this work are illustrated with practical examples of today's industrial problems.
Keywords: torus; toroidal helix; winding angle; straight helix; curved composite frame; optimized winding procedure; roving winding